Short- and medium-term survival after TAVI: Clinical predictors and the role of the FRANCE-2 score. (December 2020) - Lee, Zong Xuan; Elangovan, Senthil; Anderson, Richard; Groves, Peter
Abstract: Aim: The aim of this study was to explore the value of the FRANCE-2 score in associating with clinical outcome in the medium and short-term after TAVI and to compare its relative merits with other risk score models. Methods: 187 consecutive patients undergoing TAVI in a single UK centre were retrospectively studied. The FRANCE-2, logistic EuroSCORE, EuroSCORE II, German AV and STS/ACC TVT risk scores were calculated retrospectively and c-statistics associating with mortality were applied. Survival outcomes were compared between different risk groups according to the FRANCE-2 scores. Results: Of the 187 patients, 57.2% were male and their mean age was 80.9 ± 6.9 years. The c-index of FRANCE-2 score for predicting 30-day mortality was 0.793 (p = 0.009), for 1-year mortality 0.679 (p = 0.016) and for 2-year mortality was 0.613 (p = 0.088). The mean survival time for patients with a high FRANCE-2 score (18.6 months) was significantly less than for patients with low and moderate scores (p = 0.0004). The logistic EuroSCORE and EuroSCORE II were poorly associated with 30-day and 1-year mortality. STS/ACC TVT score was best predictive of 1-year mortality and German AV score was moderately predictive of 30-day mortality. Conclusions: The FRANCE-2 risk score is associated with differential short- and medium-term survival in patients undergoing TAVI. The presence of a high FRANCE-2 score (>5) is associated with poor survival. The FRANCE-2 scoring system could be considered as a useful additional tool by the Heart multidisciplinary team (MDT) in identifying patients who are likely to have limited survival benefit although this requires further prospective evaluation.